IDENTIFIKASI RHODAMIN B DAN METHANIL YELLOW PADA JAJANAN ANAK DI SEKOLAH DASAR DENGAN METODE KROMATOGRAFI LAPIS TIPIS - Meiria Istiana Sari; Andini (Hexagon, 2023)
Rhodamine B is a synthetic dye whose use is prohibited in cosmetics and declared a hazardous substance according to the Regulation of the Minister of Health (PerMenKes) No.239/MenKes/Per/V/1985 because it can cause liver, kidney and spleen damage followed by anatomical changes in the form of enlargement organ. Rhodamine B is often abused in food, beverage, drug and cosmetic products. This study aims to find out whether the children's snacks made from cotton candy and sand crackers contain rhodamine B. This study used a qualitative test, namely the Thin Layer Chromatography method. The principle is the absorption of the color of the woolen thread samples in an acidic environment by heating, followed by dissolving the colored woolen threads. Each sample was replicated 3 times and then compared with standard rhodamine B using eluent n-butanol : glacial acetic acid : water (4 : 5 : 1). The results showed that the 8 samples tested did not identify the presence of rhodamine B dyes. The conclusion of this study was that 8 samples of confectionery and sand crackers did not contain rhodamine B